PERAN EMOSI DALAM MEMENGARUHI KEPUASAN DAN INTENSI WORD-OF-MOUTH KONSUMEN PRODUK JASA SALON RAMBUT DI BANDAR LAMPUNG - Suprihatin Ali (SOSIOLOGI: Jurnal Ilmiah Kajian Ilmu Sosial dan Budaya, 2018)
The objective of this research is to analyze the emotional effect on consumer satisfaction and word of mouth intention in hair industry context. Emotions component are positive and negative affect. Positive affectivity refers to positive emotions and expression, including cheerfulness, pride, enthusiasm, energy, and joy. Negative affectivity is negative emotions and expression, which includes sadness, disgust, lethargy, fear, and distress. Using AMOS and field study to examine hipotheses model which is developed from previous study. Study results show that positive and negative affect that play a large role in consumer buying decision. Positive Affect have positive and significant effect on consumer satisfaction and word of mouth intention. However, Negative Affect have negative effect on consumer satisfactiion. In Contrast, Negative effect have positive effect on word of mouth intention. Moreover, Consumer satisfaction have greater contribution in expalining consumer WOM intention. The findings shows that it is important for practical implication to emphasize customer satisfaction as a strategic lever for enhancing business performance is a widespread business practice.